Daniel Heinsius’ Socrates in De contemptu mortis. The subversive fashioning of a character sui generis - Ouwerkerk, Aron (Neulateinisches Jahrbuch, 2020)
Abstract Daniel Heinsius’ didactic epic De contemptu mortis (1621) has prompted several scholars to explore which textual sources could have inspired the author in his writing. The aim of this article is to further consider one of those likely sources, namely Lucretius’ De rerum natura, by carefully juxtaposing the well-known passages on the philosopher Epicurus with Heinsius’ praise of Socrates (chiefly DCM 1.130–230). This Lucretio-Heinsian comparison will lead to a broader understanding of the special relation with Socrates that Heinsius may have had, offering textual interpretations not yet accounted for. Finally, Plato’s Phaedrus will be induced as a possible explanation for the discrepancies that do exist between Heinsius and Lucretius’ DRN. In short, what emerges is a better glimpse into the ways that one of the most prominent early modern Dutch intellectuals engaged with the classics in his own writings.